2003
DOI: 10.1016/s1044-0305(03)00450-1
|View full text |Cite
|
Sign up to set email alerts
|

Chemical ionization pathways of polyfluorinated chemicals—A connection to environmental atmospheric processes

Abstract: A systematic mass spectrometry study of an industrially prolific class of polyfluorinated compounds known as telomers was conducted. The study specifically focused upon polyfluorinated alcohols along with corresponding saturated and ␣,␤-unsaturated fluoroacids. Within each class differing fluoroalkyl chain length homologues were investigated, using negative and positive chemical ionization mass spectrometry (NCI and PCI). In the case of the fluoroalcohols, NCI resulted in the production of more elaborate spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 35 publications
2
25
0
Order By: Relevance
“…In agreement with previous studies, [21,28,29] we found several energetically stable conformers for FTOHs. These belong to two groups: stretched conformations (SCs) and conformations with an intramolecular hydrogen bond between the hydroxylic proton and fluorine attached to the C 3 carbon (electrostatically interacting conformations, EICs), Fig.…”
Section: Evaluation Of Cosmotherm Against Measured Properties Of Ftohssupporting
confidence: 93%
“…In agreement with previous studies, [21,28,29] we found several energetically stable conformers for FTOHs. These belong to two groups: stretched conformations (SCs) and conformations with an intramolecular hydrogen bond between the hydroxylic proton and fluorine attached to the C 3 carbon (electrostatically interacting conformations, EICs), Fig.…”
Section: Evaluation Of Cosmotherm Against Measured Properties Of Ftohssupporting
confidence: 93%
“…A similar intramolecular hydrogen bond can also exist in NMeFOSE and NEtFOSE [61]. This intramolecular hydrogen bonding influences the geometry of the molecule and, as such, may also influence physical properties such as vapour pressure and octanol-water or octanol-air partitioning coefficients [58,59].…”
Section: The Influence Of Fluorinementioning
confidence: 87%
“…Depending on the hydrophilic end group of the PFC, hydrogen bonding between the end group and the perfluoroalkyl chain can occur [53,[56][57][58][59][60]. For example, in the FTOHs, an intramolecular hydrogen bond can exist between the hydroxylic proton and the two fluorine atoms next to the ethanol moiety (ÀOÀH ... FÀ) [58,59].…”
Section: The Influence Of Fluorinementioning
confidence: 99%
See 1 more Smart Citation
“…Ellis et al investigated a series of PFCAs by 19 F NMR techniques. [7] They found that the polyfluorinated chains adopt a helical-twist geometry, whereas their hydrocarbon counterparts prefer a "zigzag" geometry. Altarawneh [8] examined the potential-energy surface for the self-decomposition of PFBA theoretically.…”
Section: Introductionmentioning
confidence: 99%